Biodigesters for Wastewater Treatment and Biogas Generation in Poultry Slaughterhouses - Suwerda, Bambang; Narto, Narto; Rois, Ibnu; Murti, Aliya Nugrafitra (Gema Lingkungan Kesehatan, 2025)
This study evaluates the integration of a biodigester reactor into the wastewater treatment system at a poultry slaughterhouse to improve effluent quality and produce biogas as an alternative energy source. Wastewater samples were collected before and after biodigester treatment, and the parameters analyzed included Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS), oil and grease, and pH stability. Biogas production was also monitored daily. The results showed significant reductions in COD (from 350 mg/L to 148 mg/L), BOD (from 225 mg/L to 82.4 mg/L), and TSS (from 180 mg/L to 32 mg/L), with average decreases of 57.83%, 63.38%, and 82.1%, respectively. Oil and grease levels decreased by 89.5%, although this reduction did not reach statistical significance (p=0,197). The pH values remained stable within the range of 6.0 to 9.0, supporting optimal microbial activity. Biogas production averaged 7.48 m³/hour in the morning and 6.70 m³/hour in the afternoon, demonstrating the biodigester’s capacity to generate renewable energy. The findings confirm that integrating a biodigester enhances organic pollutant removal efficiency, reduces reliance on fossil fuels, and minimizes wastewater pollution, offering both economic and environmental benefits. However, further optimization is needed to effectively reduce oil and grease concentrations. This study highlights the potential of biodigester technology as a sustainable solution for managing poultry slaughterhouse wastewater, contributing to environmental protection and energy recovery